Desperation in death [compact disc, unabridged] - Robb, J. D., 1950- (Robb, J. D., 1950- In death novel., 2022)
New York, 2061: The place called the Pleasure Academy is a living nightmare where abducted girls are trapped, trained for a life of abject service while their souls are slowly but surely destroyed. Dorian, a thirteen-year-old runaway who had been imprisoned there, might never have made it out if not for her fellow inmate Mina, who had hatched the escape plan. Mina was the more daring of the two, but they had been equally desperate. Unfortunately, they didn't get away fast enough. Now Dorian is injured, terrified, and wandering the streets of New York, and Mina lies dead near the waterfront while Lt. Eve Dallas looks over the scene. No matter what, she must keep her head clear, because she is desperate for justice and to take down those who prey on and torment the innocent.